The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5688/ajpe6355
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Entrepreneurial Intentions in Doctor of Pharmacy Students

Abstract: Objectives. A 5 factor measure (proactive disposition (PD), preference for innovation, self-esteem, achievement motivation, and nonconformity) was tested to see if it formed a single entrepreneurial drive (ED) scale, and which factors were associated with either general (GEI) or pharmacyspecific entrepreneurial intention (PEI).Methods. Over 3 years, third year Doctor of Pharmacy (PharmD) students completed a survey. Factor analysis, Cronbach's alpha, correlations, hierarchical regression analysis, and structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 56 publications
1
9
1
Order By: Relevance
“…Al Gharaibeh (2011), Caputo et al (2016 and Ramadani (2015) indicate that women in patriarchal societies face greater challenges to starting their own businesses than men, potentially because the society is relatively patriarchal. Some research indicates that EI is lower for female pharmacy students in the USA than for males (Huston, 2018). Although pharmapreneurship is not among the career choices offered in their survey, in the Jordanian context, Jarab et al (2021) observe differences in the desired career path of male and female Jordanian pharmacy students, with women showing a higher preference for working in hospital pharmacies, because they perceive these positions offer greater personal fulfillment, and males showing relatively more favorable attitudes toward working for pharmaceutical companies as the perceive that it offers greater financial rewards.…”
Section: 33mentioning
confidence: 99%
See 1 more Smart Citation
“…Al Gharaibeh (2011), Caputo et al (2016 and Ramadani (2015) indicate that women in patriarchal societies face greater challenges to starting their own businesses than men, potentially because the society is relatively patriarchal. Some research indicates that EI is lower for female pharmacy students in the USA than for males (Huston, 2018). Although pharmapreneurship is not among the career choices offered in their survey, in the Jordanian context, Jarab et al (2021) observe differences in the desired career path of male and female Jordanian pharmacy students, with women showing a higher preference for working in hospital pharmacies, because they perceive these positions offer greater personal fulfillment, and males showing relatively more favorable attitudes toward working for pharmaceutical companies as the perceive that it offers greater financial rewards.…”
Section: 33mentioning
confidence: 99%
“…Given that Jordan has embarked on a new national financial literacy program providing entrepreneurship and innovation training for all students in its primary and high schools, future research can identify the impact on the EIs of pharmacists who completed this training. Huston (2018) recommends that graduate pharmacy students take entrepreneurship courses to stimulate EI. Shahiwala (2017) describes the implementation of a successful two-credit-hour pharmacy management course in a culturally similar environment to Jordan, the Dubai Pharmacy College undergraduate program.…”
Section: Pharmapreneurial Motivation and Intentionmentioning
confidence: 99%
“…There is also evidence that a growing number of pharmacists prefer to seek business or entrepreneurial training at business schools after they have entered the workforce (Alkhateeb et al, 2012). Some important traits are a “sine qua non” for successful entrepreneurship: according to industry experts, successful innovators and entrepreneurs are those who exhibit confidence in their ability to prosper, welcome criticism, take responsibility for their failures, favor moderate risk, value achievement over money and show flexibility in their decision making process (Huston, 2018; Kerr et al, 2017). These essential character traits may be innate for some, but most aspiring entrepreneurs must learn and develop them in order to run a successful business.…”
Section: Pharmacist Impact On Healthcare Expenditurementioning
confidence: 99%
“…Entrepreneurship in a broader sense is defined as identifying and creating new opportunities within uncertain business environments (Neck & Green, 2011). A study performed among pharmacy students over a three-year period concluded that an entrepreneurship course and strong predisposition were the primary factors in IE development (Huston, 2018). Some schools and colleges of pharmacy in the USA have developed programmes to facilitate IE learning among pharmacy students.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, not all pharmacy schools are equipped with the requisite resources, nor is it their priority to provide such intensive learning opportunities. Although there are numerous reports emphasising the significance of entrepreneurial development in pharmacy students (Hermansen-Kobulnicky & Moss, 2004;Huston, 2018;Mattingly et al, 2019a), there are very few studies related to implementation and assessment of IE activities (Laverty et al, 2015;Mogul et al, 2020).…”
Section: Introductionmentioning
confidence: 99%